2016
DOI: 10.4103/0974-2069.171355
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis following coil occlusion of perimembranous ventricular septal defect with the Nit-Occlud (®) Le device

Abstract: The Nitinol coil system was recently developed by “PFM” specifically for the transcatheter occlusion of ventricular septal defects (VSD). The device consists of a coil fitted with polyester fibers designated for the closure of perimembranous defects with an aneurysmal septum and some muscular VSDs. We report a case of fatal acute infective endocarditis 10 days following the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Even though native VSD endocarditis is well known, [9] device-associated endocarditis following PmVSD closure is scarce. Up to now, only 2 cases with post procedure IE occurred 10 days [7] and 4 months [6] after transcatheter closure of PmVSD with Nit-Occlud Le device, respectively, have been reported. To our knowledge, this is the first case of IE complicated by residual shunt after percutaneous PmVSD occlusion using modified symmetric double-disk occluder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though native VSD endocarditis is well known, [9] device-associated endocarditis following PmVSD closure is scarce. Up to now, only 2 cases with post procedure IE occurred 10 days [7] and 4 months [6] after transcatheter closure of PmVSD with Nit-Occlud Le device, respectively, have been reported. To our knowledge, this is the first case of IE complicated by residual shunt after percutaneous PmVSD occlusion using modified symmetric double-disk occluder.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Post-procedure IE after transcatheter closure of PmVSD is rarely reported. [6,7] Herein, we first described a case of IE after transcatheter closure of PmVSD with modified symmetrical double-disk device with a residual shunt, highlighting the need for reassessing the prognostic implications of post procedure non-significant residual shunt and the most appropriate treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[14151617] A study of 125 patients with isolated VSD who were followed up for a mean of 15 years showed no statistical difference in the incidence of bacterial endocarditis between the untreated patients (4.3%) and those that were surgically closed (2.7%) although the sample size of the study was small. [18] The Swedish registry data also showed an incidence of endocarditis of 1.2% in patients who had undergone surgery for VSD versus an overall incidence of 2% in the entire group.…”
Section: What Is the Incidence Of Infective Endocarditis In Patients mentioning
confidence: 99%
“…Ventricular septal defect (VSD) is one of the most common types of congenital cardiac disease (CHD) in children especially perimembranous variant [2]. Surgical closure of VSD carries a low risk of morbidity and mortality, however transcatheter closure is less invasive, has a faster recovery and requires less hospital stay period [3]. Transcatheter VSD closure has been developed in order to reduce surgical complications [4].…”
Section: Introductionmentioning
confidence: 99%